2013
DOI: 10.1007/s12272-013-0198-z
|View full text |Cite
|
Sign up to set email alerts
|

Antityrosinase and antimicrobial activities from Thai medicinal plants

Abstract: Various dermatological disorders and microbial skin infection can cause hyperpigmentation. Therefore, screenings for whitening and antimicrobial agents from Thai medicinal plants have been of research interest. Seventy-seven ethanol plant extracts were investigated for antityrosinase activity, eleven samples showed the tyrosinase inhibition more than 50 % were further preliminary screening for antimicrobial activity by agar disc diffusion and broth micro-dilution methods. Artocarpus integer (Thunb.) Merr. (Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…According to the increase in DE and a ⁄ values and the decrease in L ⁄ value normally associated with browning, all the results combined revealed that 0.01% Arto + 0.05% VcME and 0.01% Arto + 0.02% VcME could better inhibit the happening of browning for apple juices than ArtoME and VcME alone. Although inhibitory effect of Arto on tyrosinase has previously been reported in our previous study (Zheng et al, 2008) and others (Arung et al, 2006;Dej-Adisai et al, 2014;Wei et al, 2005), the mechanism of its browning inhibition is still unknown. The above findings suggested that browning inhibition of Arto was achieved possibly through a mechanism similar to that of 4-HR.…”
Section: Tablementioning
confidence: 74%
See 2 more Smart Citations
“…According to the increase in DE and a ⁄ values and the decrease in L ⁄ value normally associated with browning, all the results combined revealed that 0.01% Arto + 0.05% VcME and 0.01% Arto + 0.02% VcME could better inhibit the happening of browning for apple juices than ArtoME and VcME alone. Although inhibitory effect of Arto on tyrosinase has previously been reported in our previous study (Zheng et al, 2008) and others (Arung et al, 2006;Dej-Adisai et al, 2014;Wei et al, 2005), the mechanism of its browning inhibition is still unknown. The above findings suggested that browning inhibition of Arto was achieved possibly through a mechanism similar to that of 4-HR.…”
Section: Tablementioning
confidence: 74%
“…It was reported to have activities of antiinflammatory, antimicrobial, and inhibitory effect on melanin biosynthesis (Arung et al, 2006;Dej-Adisai et al, 2014;Wei et al, 2005). Our previous study revealed that Arto had strong tyrosinase inhibitory activity (Zheng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitutions of an isoprenyl group on C-3, a 3-methyl-1-butenyl group on C-6, and a hydroxy group on C-2 0 for cycloartocarpin (1) and artocarpin (2) might be required for their antibacterial activity (Dej-adisai et al, 2013;Tsuchiya et al, 1996). Cyclization of the hydroxy group on C-2 0 with the isoprenyl group on C-3 for cycloartocarpin (1) resulted in a decrease of antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…1) from the heartwoods of A. heterophyllus. 6 Artocarpanone also possessed antiinflammatory activity and had an inhibitory effect on melanin biosynthesis 7,8 , while artocarpin possessed anticancer activity and inhibited neuraminidase 9,10 , while cycloartocarpin possessed antiplatelet activity.…”
Section: -5mentioning
confidence: 99%